IMPACT OF SOCIAL MEDIA ON STUDENTS’ ACADEMIC PERFORMANCE: A CASE STUDY OF ISLAMIC UNIVERSITY, BANGLADESH - Uddin, Md. Kamal; Huda, Md. Nazmul; Ali, Md. Jafor; Alam, Md. Shahbub; Bhuiyan, Abul Bashar (American Economic & Social Review, 2022)
Social media is a globally known and widely used means of social communication that has brought most people very close in today's world especially the Z generation or iGen who are more familiar and attracted to this medium. Among them are university students who mostly prefer to spend time on it and as a result, it might have either positive or negative effects on their academic studies. The current study aims to investigate the effect of social media on the academic performance of university students in Bangladesh. A well-structured questionnaire is used to collect data from 150 students of Islamic University, Kushtia, Bangladesh and they are selected based on a convenient sampling procedure. Both descriptive and inferential statistics are applied to analyze the data. The study found that 73% of students engaged in social media for non-academic purposes and most of them visited the Facebook site. The study also found that the majority of the students visit social networking sites at home, and in residential halls, while most of them spend time on average more than four hours daily, and mostly from 6.00 pm to 6.00 am. The study reveals that time spent on social media and excessive usage of social media negatively impacts students’ academic performance. The study recommends that parents, teachers, and students’ advisor in the university guide and monitor students properly so that they can’t misuse social media.JEL Classification Codes: C12, C83, C88, I29.